2020
DOI: 10.3390/genes11080908
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Methylated lncRNAs-Based Prognostic Signature for Hepatocellular Carcinoma

Abstract: Currently, an increasing number of studies suggest that long non-coding RNAs (lncRNAs) and methylation-regulated lncRNAs play a critical role in the pathogenesis of various cancers including hepatocellular carcinoma (HCC). Therefore, methylated differentially expressed lncRNAs (MDELs) may be critical biomarkers of HCC. In this study, 63 MDELs were identified by screening The Cancer Genome Atlas (TCGA) HCC lncRNAs expression data set and lncRNAs methylation data set. Based on univariate and multivariate surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Three previously published HCC-related signatures derived from TCGA successfully and significantly predict the OS outcomes, including five-ARG signature (HDAC1, RHEB, ATIC, SPNS1, and SQSTM1) by Huo et al ( 2020 ) four-lncRNA signature (ENSG00000234608, ENSG00000242086, ENSG00000273032, ENSG00000228463) by Yang et al ( 2020 ) and four-lncRNA signature (RP11-322E11.5, RP11-150O12.3, AC093609.1, CTC-297N7.9) by Wang et al ( 2017 ). To compare the sensitivity and specificity of our five-AR-lncRNA signature for the prognosis prediction with these three existing signatures, we performed the time-dependent ROC analysis (Liao et al, 2020 ). The AUCs of 3-year OS for Hou's signature, Yang's signature, and Wang' signature was 0.655, 0.504, and 0.704, respectively, all of which were lower than that of our five-AR-lncRNA signature (AUC = 0.751) ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Three previously published HCC-related signatures derived from TCGA successfully and significantly predict the OS outcomes, including five-ARG signature (HDAC1, RHEB, ATIC, SPNS1, and SQSTM1) by Huo et al ( 2020 ) four-lncRNA signature (ENSG00000234608, ENSG00000242086, ENSG00000273032, ENSG00000228463) by Yang et al ( 2020 ) and four-lncRNA signature (RP11-322E11.5, RP11-150O12.3, AC093609.1, CTC-297N7.9) by Wang et al ( 2017 ). To compare the sensitivity and specificity of our five-AR-lncRNA signature for the prognosis prediction with these three existing signatures, we performed the time-dependent ROC analysis (Liao et al, 2020 ). The AUCs of 3-year OS for Hou's signature, Yang's signature, and Wang' signature was 0.655, 0.504, and 0.704, respectively, all of which were lower than that of our five-AR-lncRNA signature (AUC = 0.751) ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these dysregulated lncRNAs, some have the potential to be critical biomarkers for early detection and prognosis prediction 26 , 27 . To date, several lncRNA prognostic models have been proven to enhance the prognostic performance of different cancers 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…One predictive model, published by Sui's study (Sui's model), consisted of four lncRNA-related signatures using the TCGA cohort (LINC00261, TRELM3P, GBP1P1, and CDKN2B-AS1) [19]. Another predictive model, derived from Liao's study (Liao's model), included four lncRNA-related signatures (AC025016.1, LINC01164, LINC01183 and LINC01269) using the TCGA cohort [20]. Our results showed that the AUC of one year of our predictive model is 0.739, which is superior to those of Sui's model (AUC: 0.600) and Liao's model (AUC: 0.635) (Figure 5A).…”
Section: Performance Comparison In Prognostic Predictionmentioning
confidence: 99%